(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Data analytics is playing an important role in e-commerce, in which classification algorithms like linear regression and random forest help in buying and selling the product as per market demand. Customer needs identification is a very challenging task. In this proposed work, we have developed an algorithm to predict the price of a car based on the various attributes of the car. In this work, two algorithms—linear regression and random forest—were implemented that can predict the correct market value of a car model for the considered data set, and the results are compared using various statistical parameters.